Aflatoxin Detoxification Potential of Ocimum Tenuiflorum. Issue 3 (26th May 2013) - Panda, Pragyanshree; Mehta, Alka
Abstract Aflatoxins are the secondary toxic metabolites produced by a group of toxigenic fungi. They are the common contaminants of food and feed that cause severe economic and health losses. The present study concerns control of aflatoxin B1 (AFB1) synthesis from Aspergillus flavus, direct degradation of AFB1 and its decontamination on rice by the aqueous extract of Ocimum tenuiflorum. In the presence of Ocimum extract, the culture of A. flavus in yeast extract sucrose medium showed an increase in mycelium mass and reduction in AFB1 production up to 64%. The direct treatment of AFB1 with extract at 85C for 4 h led to 74.7% degradation. Whereas in rice spiked with AFB1, the degradation was 70.2%. This degradation resulted in detoxification, which was confirmed using mammalian cell culture method. The results of the study showed that Ocimum extract can be used efficiently to eliminate the AFB1 threat. Practical Applications Mycotoxin contamination of food and feed is a major concern in food and agricultural sector. Continuous research in the area of physical and chemical methods to eliminate mycotoxin is being carried out but there is a need to find more safe natural agents to reduce the mycotoxin threat. This study demonstrates the efficacy of Ocimum as a safe additive, which not only inhibits the aflatoxin production but also degrades the existing toxin. Hence, the Ocimum can be safely used for the reduction and removal of aflatoxin to the safe level from the food and feed chain.